Motivation Factors Affecting the Decision to Participate in Recreational Activities of Rajamangala University of Technology Phra Nakhon Students After the COVID-19 Crisis. - Thanomphichai, Karoon; Nimnatipun, Sumanontri (Journal of Faculty of Physical Education, 2024)
The aim of this research is to study the motivational factors affecting the decision to participate in recreational activities of students at Rajamangala University of Technology Phra Nakhon after the COVID-19 crisis. The sample group used in this research Including students from Rajamangala University of Technology Phra Nakhon, 3 faculties: Faculty of Business Administration Faculty of Liberal Arts and the Faculty of Textile Industry and Fashion Design, Years 1 - 4, totaling 375 people. The research instrument was a questionnaire on motivational factors affecting the decision to participate in recreational activities of students at Rajamangala University of Technology Phra Nakhon after the COVID-19 crisis. Statistics used in data analysis in research include frequency, percentage, mean, and standard deviation. and statistics used to find the Pearson relationship. The research results found that Motivational factors affecting the decision to participate in recreational activities of Rajamangala University of Technology Phra Nakhon students after the COVID-19 crisis. Overall it was equal to 0.41, meaning that different internal and external factors had different effects on the decision to participate in recreational activities. with statistical significance at .05